Dental Calculus: A Bacterial Hub - Rajiv Saini (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
The Surgeon General's report on oral health highlights the relationship between oral and overall health, emphasizing that oral health involves more than dentition [1]. Mouth acts as a window to lot of systemic diseases and serves as a port of entry of the various infections that can alter and affect the immune status of the person. The oral cavity has the potential to harbour at least 600 different bacterial species, and in any given patient, more than 150 species may be present, surfaces of tooth can have as many as billion bacteria in its attached bacterial plaque and oral care may not only reduce the microbial load of the mouth but the risk for pain and oral infections as well [2]. Bacterial deposition starts immediately within few hours on cleaned tooth surface and with eventual period of time layering and inter-locking of microbiological colonies lead to development of dental plaque. The process of plaque formation at microscopic level represents a highly ordered and predictable ecological succession and can be divided into three phases as illustrated in Figure 1.